“I CAN’T RESIST TIKTOK”: EXPLORING THE INFLUENCE OF CELEBRITY ENDORSEMENT, PARASOCIAL INTERACTION, AND FOMO ON GEN-Z PURCHASE INTENTION - Oktavian, Rizal Boy; Dermawan, Rizky; Majid, Nurkholish (Universitas Nusa Cendana, 2024)
This research aimed to examine the influence of celebrity trustworthiness, celebrity attractiveness, parasocial interaction, and fear of missing out (FOMO) on purchase intention among TikTok users in the management student community. The population consisted of active undergraduate management students at the Universitas Pembangunan Nasional